Teacher Characteristics and Pupil Performance in Science and Health in the National Achievement Test of Iligan City Division - Hinay, Joveniana C. (JPAIR Multidisciplinary Research, 2010)
The research determined the educational qualification, experience, and the level of training objectives attainment of science teachers in relation to the level of performance of Grade VI pupils in Science and Health in the National Achievement Test (NAT) during the school year 2008-2009 of the rural and urban schools in the Division of Iligan City. The study used the descriptive research design and employed the 81 grade VI science teachers, 71 school administrators and 125 sample pupil respondents to answer the researcher- made questionnaire Data drawn from the data gathering process were analyzed using mean, t-test and multiple regression. Science teachers are not so interested about their own advance education. Science teachers are averagely experienced in teaching the subject. They highly attained the training objectives of the seminars they had attended. The advance education, experiences and the attainment of the training objectives of teachers did not affect the way pupils performed in the NAT.
Keywords: Teacher Characteristic; Science and Health Result; National Achievement test